2011
DOI: 10.1007/s13562-011-0039-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers linked with bruchid resistance in Vigna radiata var. Sublobata and their validation

Abstract: Bruchid, Callosobruchus chinensis (L.) is an important pest of Vigna radiata during storage. RFLP and PCR based markers identified, linked with bruchid resistance gene in wild accession of greengram (V. radiata var.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The authors reported close linkage in a recombinant inbred line (RIL) population between ACC41 and ‘Berken’. Further, Sarkar et al (2011) showed that STSbr1 amplified a 225bp fragment in V. sublobata accession (sub2) and 12 other cultivars that were resistant to bruchids. Though RAPD markers are fast and simple, the distance between them is high from the bruchids resistant gene.…”
Section: Sources Of Resistance Against Insect-pestsmentioning
confidence: 99%
“…The authors reported close linkage in a recombinant inbred line (RIL) population between ACC41 and ‘Berken’. Further, Sarkar et al (2011) showed that STSbr1 amplified a 225bp fragment in V. sublobata accession (sub2) and 12 other cultivars that were resistant to bruchids. Though RAPD markers are fast and simple, the distance between them is high from the bruchids resistant gene.…”
Section: Sources Of Resistance Against Insect-pestsmentioning
confidence: 99%
“…Great efforts have been invested in mapping a Br gene in mungbean [ 19 ]. First, a single Br gene was proposed in TC1966, and later additional minor modifier factors were postulated [ 16 , 17 , 44 ]; nevertheless, the nature of the Br gene(s) of TC1966 remained unclear. Biochemically, several Br candidate genes highly associated with bruchid resistance have been reported, including the Va gene for vignatic acid biosynthesis [ 20 ]; vicilins, also known as 7S storage globulins [ 22 ]; and the cysteine-rich protein VrD1 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…sublobata accession ( Sub2 ) and also in some of the mung bean cultivars with contrasting host response to bruchid infestation. It behaves as a dominant marker among the Indian genotypes, and is efficiently used for screening bruchid‐resistant genotypes (Sarkar et al ., ). Blair et al .…”
Section: Biotechnological Approachesmentioning
confidence: 97%
“…Only in mung bean, a STS marker ( STSbr1 ) which was reported to be associated with the bruchid resistance gene in the Australian V. radiata var. sublobata ( ACC41 ), was validated among the Indian sublobata accession ( Sub2 ) and mung bean cultivars conferring bruchid resistance (Sarkar et al ., ). The utilisation of this marker in the MAB (Man and the Biosphere) programmes of mung bean is under progress.…”
Section: Biotechnological Approachesmentioning
confidence: 97%
See 1 more Smart Citation